Perancangan Aplikasi Service Reminder Sepeda Motor Berbasis Android Mobile - Yosia Kehat Driesa; Ramos Somya (JATISI (Jurnal Teknik Informatika dan Sistem Informasi), 2023)
Motorcycle is a means of transportation that is widely used in Indonesia. There is an increase in the number of motorcycle users. The growth in the number of motorised vehicles in Indonesia has a negative impact, including air pollution, traffic jams, accidents, and etc. The number of accident cases in Indonesia is the highest compared to other modes of transportation. The causes of accidents are generally caused by several factors, including not being careful, negligent or forgetting to do routine services. The purpose of this research is to design a routine service reminder application for motorcycle spare parts based on android mobile which will be used by motorcycle users. The method in making this mobile application uses the extreme programming model. The resulting mobile service reminder application is then tested using black-box testing to determine the success rate of the designed application, and the test results show that the application can run well. The result of this research is a routine motorcycle service reminder application based on Android mobile using the Javascript programming language, React Native framework, Firebase database. This application can be a solution to the problems faced by motorcycle users, namely being negligent or forgetting the routine service schedule.